A serological, parasitological and clinical evaluation of untreated Chagas disease patients and those treated with benznidazole before and thirteen years after intervention - Girley Francisco Machado-de-Assis; Glaucia Alessio Diniz; Roberto Araujo Montoya; Joao Carlos Pinto Dias; Jose Rodrigues Coura; George Luiz Lins Machado-Coelho; Pedro Albajar-Vinas; Rosalia Morais Torres; Marta de Lana (Memorias do Instituto Oswaldo Cruz, 2013)
The etiological treatment of Chagas disease is recommended for all patients with acute or recent chronic infection, but controversies remain regarding the benefit of chemotherapy and interpretations of the parasitological cure after etiological treatment. This study compares the laboratory and clinical evaluations of Chagas disease patients who were diagnosed 13 years earlier. Fifty-eight Chagas disease patients (29 treated with benznidazole and 29 untreated) were matched at the time of treatment based on several variables. Conventional serology revealed the absence of seroconversion in all patients. However, lower serological titres were verified in the treated group, primarily among patients who had the indeterminate form of the disease. Haemoculture performed 13 years after the intervention was positive for 6.9% and 27.6% of the treated and untreated patients, respectively. Polymerase chain reaction tests were positive for 44.8% and 13.8% of the treated and untreated patients, respectively. Patients who presented with the indeterminate form of the disease at the beginning of the study exhibited less clinical progression (17.4%) compared with the untreated group (56.5%). Therefore, this global analysis revealed that etiological treatment with benznidazole may benefit patients with respect to the clinical progression of Chagas disease and the prognosis, particularly when administered to patients with the indeterminate form of the disease.